2006
DOI: 10.1002/cncr.22439
|View full text |Cite
|
Sign up to set email alerts
|

Is there a role for platinum chemotherapy in the treatment of patients with hormone‐refractory prostate cancer?

Abstract: Docetaxel chemotherapy is the current standard of care for metastatic hormone-refractory prostate cancer (HRPC). Platinum chemotherapy drugs, such as cisplatin and carboplatin, have moderate single-agent activity in HRPC. Next-generation platinum drugs, including satraplatin and oxaliplatin, may have additional activity in the management of HRPC. Furthermore, neuroendocrine differentiation may play a role in disease progression, providing a rationale for platinum-based chemotherapy in the management of HRPC. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
40
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 62 publications
(40 citation statements)
references
References 93 publications
0
40
0
Order By: Relevance
“…Until recently, HRPC has been widely considered resistant to chemotherapy, including cisplatin and carboplatin (46), although these studies were limited by traditional measures of radiographic response for treatment assessment (47). Two recent landmark trials, however, showed that docetaxel-based chemotherapy afforded statistically significant improvements in overall survival, prostate-specific antigen (PSA) response, pain relief, and quality of life, setting a new standard of care for HRPC patients (48,49).…”
Section: Clinical Trialsmentioning
confidence: 99%
“…Until recently, HRPC has been widely considered resistant to chemotherapy, including cisplatin and carboplatin (46), although these studies were limited by traditional measures of radiographic response for treatment assessment (47). Two recent landmark trials, however, showed that docetaxel-based chemotherapy afforded statistically significant improvements in overall survival, prostate-specific antigen (PSA) response, pain relief, and quality of life, setting a new standard of care for HRPC patients (48,49).…”
Section: Clinical Trialsmentioning
confidence: 99%
“…Use of capecitabine instead of infusional 5-fluorouracil (ECX) has been at least as effective as ECF in esophagogastric cancer. 15 Oh and colleagues 16 reviewed the use of platinum-based chemotherapy in CRPC and identified objective response rates ranging from 45% to 65% with combinations of estramustine, carboplatin, and either paclitaxel or docetaxel in 6 phase II trials. In a subsequent report studying docetaxel plus carboplatin, the objective response rate was 25% in chemonaive patients who also received with estramustine, and 8% in patients progressing despite docetaxel.…”
Section: Discussionmentioning
confidence: 99%
“…A phase III trial of satraplatin, an oral platinum that inhibits replication through the formation of DNA adducts, has demonstrated activity as a second line chemotherapy for patients with androgen-independent disease (77). The increased understanding of the relationship between DNA and chromatin structural proteins has led to the development of histone deacetylase inhibitors such as suberoylanilide hydroxamic acid (vorinostat), which interferes with chromatin unfolding and subsequent gene activation (78).…”
Section: Figurementioning
confidence: 99%